Study of the influence of medication properties and lifestyle of patients with coronary heart disease on adherence to treatment - Dolzhenko, M. M.; Bilousova, N. A.; Mykhalchuk, V. M.; Tkachenko, N. O.; Luchinskaya, Yu. O.; Ткаченко, Наталя Олександрівна (My University, 2025)
Aim: To investigate how lifestyle factors of patients with CHD and comorbid conditions, along with medicines properties, influence treatment adherence. Materials and Methods: include the results of a survey conducted among patients with CHD and comorbid conditions at the Department of Cardiology of the P.L. Shupyk National Healthcare University of Ukraine from June to September 2024 (n = 101). The study employed methods of analysis, synthesis, deduction, induction, comparison, statistical and bibliographic research. Results: The study revealed a significantly low adherence rate of 13.9% [CI 95% 13.9 ± 0.002; p<0.0001] to risk factor modification and prescribed pharmacotherapy in secondary prevention of CHD. It confirmed a statistically significant influence of patient preferences with CHD and comorbid conditions on effective pharmacotherapy (χ2 = 3.350,232, p = 0.067). Patients receiving consultations from both doctors and pharmacists were 22 times more likely (OR = 22.67) to adhere to pharmacotherapy compared to those consulting only doctors. The study found that only 7.8% [CI 95% 7.8 ± 0.05; p<0.0001] of surveyed patients with CHD and comorbid conditions such as hypertension, diabetes mellitus and chronic kidney disease utilized the “Affordable Medicines” program. Conclusions: The decline in the socioeconomic status of the population during the war in Ukraine negatively affects adherence to clinical guidelines for risk factor modification and secondary prevention of CHD, as evidenced by observational studies EUROASPIRE IV and V. The study identified that 42.8% of respondents prefer original medicines when selecting medications, but financial constraints prevent prolonged use as part of prescribed pharmacotherapy, adversely affecting treatment adherence. The effectiveness of a multidisciplinary approach in enhancing treatment adherence among patients with CHD and comorbid conditions was confirmed, demonstrating a 22-fold higher adherence rate compared to consultations with doctors alone.
Keywords: Coronary heart disease; treatment adherence; pharmaceutical care; multidisciplinary team; generic medicines; original medicines